1985
DOI: 10.1055/s-2007-1018461
|View full text |Cite
|
Sign up to set email alerts
|

Double Early Epidermoid Carcinoma of the Esophagus in Columnar Epithelium

Abstract: Two epidermoid, identical but independent tumors of the middle esophagus, arising in columnar lined esophagus (Barrett's esophagus or endobrachyesophagus) are reported. Both were diagnosed endoscopically and resected. The upper tumor involved only the mucosa, the aboral one the mucosa and submucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It has been suggested to have developed initially as SCC, and then into ASC as a result of a subsequent occurrence of glandular metaplasia, or may also have been primarily an adenocarcinoma with areas of squamous metaplasia in tumor cell differentiation. 4,17 Some authors infer the collision concept, which hypothesizes that two individual stem cells may have simultaneously and independently undergo malignant Esophageal adenosquamous carcinoma 787 transformation. 5,18,19 However, some authors posited that the tumor may also have arisen from the mucous epithelium of a Barrett's esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested to have developed initially as SCC, and then into ASC as a result of a subsequent occurrence of glandular metaplasia, or may also have been primarily an adenocarcinoma with areas of squamous metaplasia in tumor cell differentiation. 4,17 Some authors infer the collision concept, which hypothesizes that two individual stem cells may have simultaneously and independently undergo malignant Esophageal adenosquamous carcinoma 787 transformation. 5,18,19 However, some authors posited that the tumor may also have arisen from the mucous epithelium of a Barrett's esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Esophagitis has been reported in some patients with BN; however, Kiss et al suggested that chronic and self-induced vomiting rarely leads to mucosal injury [51]. Several case reports described Barrett's and carcinoma of the esophagus in patients with a prior history of BN or psychogenic vomiting [52,53]. Conversely, a recent study demonstrated that patients with ED had an increased risk of developing esophageal cancer but no cases were adenocarcinomas.…”
Section: Bulimia Nervosamentioning
confidence: 99%
“…Its histogenesis is controversial. The tumor may derive from Barrett's esophagus, or may have a mixed origin arising from both squamous and glandular epithelium simultaneously, or may be primarily an adenocarcinoma with areas of squamous metaplasia or primarily a squamous carcinoma with glandular metaplasia [15,16]. The absence of Barrett's esophagus around the tumor and the prevalent squamous structure suggest that the adenosquamous tumor had a unique origin from superficial esophageal epithelium.…”
Section: Discussionmentioning
confidence: 99%